Using Co-Culture to Functionalize Clostridium Fermentation - Cui, Yonghao; Yang, Kun-Lin; Zhou, Kang (Trends in biotechnology (Regular ed.), 2021)
Clostridium fermentations have been developed for producing butanol and other value-added chemicals, but their development is constrained by some limitations, such as relatively high substrate cost and the need to maintain an anaerobic condition. Recently, co-culture is emerging as a popular way to address these limitations by introducing a partner strain with Clostridium. Generally speaking, the co-culture strategy enables the use of a cheaper substrate, maintains the growth of Clostridium without any anaerobic treatment, improves product yields, and/or widens the product spectrum. Herein, we review recent developments of co-culture strategies involving Clostridium species according to their partner stains’ functions with representative examples. We also discuss research challenges that need to be addressed for the future development of Clostridium co-cultures. Clostridium co-culture has emerged as a solution to some problems faced by Clostridium monoculture.Co-culturing Clostridium with cellulolytic strains or acetogens enables the production of butanol from cheaper substrates such as lignocellulosic biomass and syngas.Aerotolerance is possible in anaerobic Clostridium fermentation in co-cultures with oxygen-consuming microbes.Co-culturing solventogenic Clostridium with acetogens can improve the production of butanol and its derivatives by increasing carbon recovery and relieving solvent toxicity.Other products, such as H2 or fatty acids, can be efficiently produced by the co-culture of Clostridium and other H2-producing strains (such as PNS bacteria), or chain-elongating strains respectively.